FORMATION OF A INTEGRATED PICTURE OF THE WORLD IN STUDENTS THROUGH THE CONTENT OF EDUCATIONAL ACTIVITIES (Pedagogy of Higher and Secondary Education, 2009)
It considers important progressing aspects of educational activity as an indispensable condition of valuable unutilitarian student's education. It actucions theme of self-control educational activity beginning since starting years of study at high school.